POLITICAL ECONOMIC ANALYSIS OF RICE SELF-SUFFICIENCY IN INDONESIA - Sri Nuryanti; Dedi Budiman Hakim; Hermanto Siregar; M. Husein Sawit (Indonesian Journal of Agricultural Science, 2017)
Rice self-sufficiency is an important programme in Indonesia. The programme has four major targets, i.e. increasing production, stabilizing prices and reserve stocks, and minimizing import. For that purpose, the government gave a mandate to a parastatal, namely National Logistic Agency (Bulog) in implementing the rice policies. Some studies found that involvement of such a parastatal could lead to government failure in budget allocation. The study aimed to estimate social cost of rice self-sufficiency programme based on the implementation of rice instrument policies by Bulog. The study used the national annual data of 2002–2014 period. The method used was the political preference function model to estimate economic rent and dead-weight loss using rice price elasticity of demand and supply. The result showed that in terms of percentage of food security budget, the average of economic rent reached IDR 6.37 trillion per annum (18.54%), while the average of dead-weight loss amounted at IDR 0.90 trillion per annum (2.34%). It proved that rice self-sufficiency programme along with the involvement of Bulog was economically inefficient. The government should provide better agricultural infrastructure, review governmental procurement prices, and stop rice import policy to remedy market failure.